Aplikasi Caring Assistance Untuk Manula Berbasis Android Dan Raspberry Pi - Fenny Destasia Chan; Andreas Handojo; Justinus Andjarwirawan (Jurnal Infra, 2018)
The presence of Nursing Home is a place chosen by some elderly families who have a solid activity. The Nursing Home is considered a new home or new environment for the elderly. For that it needs special attention to the elderly living in the Panti Werdha. A 24-hour service by accompanying staff and scheduled listing systems is a way to lead an elderly health. But in the belief, not all elderly nurses can be maintained for 24 hours. Because of the limitations of human ability that is sleeping or not, always guard near the elderly It can be dangerous seniors need help in the middle of the night.Seeing the problem, then needed a technology that could be between seniors and elderly nurses. And serves as a helper in maintaining the health of the elderly. Caring Assistance app using Android and Raspberry Pi. Seniors who need help, can press the switch later will appear notification to mobile run and display live streaming video. Elderly nurses can be more responsive in providing emergency assistance. This application can help seniors with the schedule of elderly drug, as well as make a list of the nearest hospital and pharmacy using the Google Places API facility on the user's mobile phone. From the results of application testing and Raspberry Pi can be concluded the application can answer the needs of elderly nurses in the elderly health care and the state of the elderly using Raspberry Pi.